How To Be An Ideal Teacher? : A Content Analysis of Ki Hadjar Dewantara’s Thoughts - Taufikin, Taufikin (Faculty of Education and Teacher Training of UINSI Samarinda, 2021)
The Industrial Revolution 4.0 era to the Society 5.0 era requires adaptation for the teacher’s competencies. So, the primary objective of this paper is to look into Ki Hadjar Dewantara's thoughts on the qualifications to be an ideal teacher. This study is a content analysis of Ki Hadjar Dewantara's thoughts regarding teachers. The result, according to Ki Hadjar Dewantara, suggests that education necessarily requires the presence of a teacher who meets comprehensive competency qualifications, particularly the exoteric/outer and esoteric/inner dimensions. Teacher has both physical (body) and intellectual (rationale) intelligence, while the esoteric dimension is a pure heart and noble character. A teacher's mandatory task is to educate in the three centers of education: family, school, and community, with comprehensive competencies should be introduced to the four teacher competencies (pedagogic, personality, professional, and social), and two dimensions competencies (esoteric and exoteric). So that teachers can recognize students with a noble character, an intelligent conscience, and are physically healthy in their daily lives.